Identification of Functional Requirements of Tools Supporting Production Planning in ME Companies - Damian OSTROWSKI; Marek GURAK (Communications of International Proceedings, 2023)
Production planning plays a key role in a manufacturing process. A well-built planning system enables effective synchronisation of the resources held by a production company in relation to the demand for finished goods. Manufacturing companies are looking for tools, methods that enable efficient and functional planning in the production area. The main motivation behind conducting the research was the desire to learn about the needs of production planners in the field of production planning and management. The research results are important due to the research gap in the field of production planning. The research found that the main priority for manufacturing companies is to focus on serving all orders without losing any customers. In the day-to-day work of manufacturers, the emphasis is also put on meeting the expected delivery date, while at the same time giving the customer the confidence that they will receive the ordered goods on time. At the same time, these companies are aware that variability of production forces them to look for solutions that, firstly, balance this variability and make the production process more flexible, and secondly, make it possible to serve each customer. The conclusions were drawn on the basis of the conducted research survey.
Keywords: production planning; SMEs; information systems